EARNİNGS QUALİTY AND FİRM VALUE: THE CASE OF BORSA ISTANBUL (Third Sector Social Economic Review, 2023)
Earnings quality is an indicator of the company's current and potential performance. Shares of higher earnings quality companies are expected to perform better. In this study, unlike other studies carried on Borsa Istanbul, an aggregated approach has been adopted in determining the earnings quality. While generating the earnings quality ranking, ""Net Profit Margin"", ""Cash Cycle"", ""Working Capital Accruals"", ""Cash Flow Based Accruals"" and ""Profit Stability"" characteristics of companies were taken into consideration. The returns of the created portfolios based on the earnings quality of the companies in the BIST-100 index were examined. It has been showed that the high-earnings quality portfolio outperforms the low-earnings quality portfolio. Even when risk is taken into account, higher earnings quality portfolio performs better. One of the important results of the research is that return of high-earnings quality portfolio and the return of low-earnings quality portfolio vary by macroeconomic conditions. In periods when economic indicators improve, the difference between returns of two portfolios decreases; on the contrary, the difference between returns increases in periods when the indicators deteriorate. Findings on market conditions and returns on earnings quality portfolios are important for Borsa Istanbul literature, which is an unexplored field of study. The results of the research suggest creating portfolios based on earnings quality, following the investment strategy and making changes in the strategy according to market expectations. In Borsa Istanbul, it is possible to earn more returns with a systematic approach based on earnings quality.
Keywords: Earnings Quality; Firm Value; Earnings Management; Investor Protection